2010
DOI: 10.1021/cg1010117
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole Cocrystals with Dicarboxylic Acids

Abstract: Fluconazole cocrystals were prepared with the intention to modify physicochemical properties of the antifungal agent. The well-known COOH···Narom heterosynthon was considered the key element in the cocrystals design strategy. Cocrystals of fluconazole with maleic, fumaric, and glutaric acid were identified in solution evaporation experiments with pharmaceutically acceptable dicarboxylic acids and their crystal structures are presented. Solid-state NMR as an alternative technique for providing structural inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 58 publications
2
38
0
Order By: Relevance
“…Both molecules presented a planar conformation on the 4‐arylimidazolic moiety, which was evaluated considering the dihedral angle between the mean least square planes that contained the imidazole and benzene rings. Additionally, the hydroxyethyl group (CH 2 CHOH) of 6 favored intermolecular hydrogen interactions, which contributed to directing the principal fragments of the molecules to form a parallel conformation, as well as occurs in some antifungal azoles of clinical use ,. The crystallographic data and a deeper description of the crystal structures are provided in the Supplementary Information.…”
Section: Resultsmentioning
confidence: 99%
“…Both molecules presented a planar conformation on the 4‐arylimidazolic moiety, which was evaluated considering the dihedral angle between the mean least square planes that contained the imidazole and benzene rings. Additionally, the hydroxyethyl group (CH 2 CHOH) of 6 favored intermolecular hydrogen interactions, which contributed to directing the principal fragments of the molecules to form a parallel conformation, as well as occurs in some antifungal azoles of clinical use ,. The crystallographic data and a deeper description of the crystal structures are provided in the Supplementary Information.…”
Section: Resultsmentioning
confidence: 99%
“…Similar systems such as miconazole (MCZ), ketoconazole (KTZ), econazole (ECZ) and tioconazole (TCZ) are antifungal imidazoles that have not only the imidazole ring, but also the 2-haloaryl-2-alcoxyethyl group at position 1 (Borgers, 1980;Fromtling, 1988;Di Santo et al, 2005;Espinel-Ingroff, 2009;Strushkevich et al, 2010;Emami et al, 2017). This moiety is also part of the antifungal triazoles itraconazole (ITZ), voriconazole (VCZ) and fluconazole (FLZ), but these have a hydroxyl instead of an alcoxyl group (White et al, 1998;ISSN 2052-5206 # 2019 International Union of Crystallography Kathiravan et al, 2012;Shrestha et al, 2017;Kastelic et al, 2010;Tsutsumi et al, 2011;Dayo-Owoyemi et al, 2019). Interestingly, the hydroxyl group of these antifungals favors hydrogen-bond interactions that contribute to directing the heterocyclic and haloaryl moieties to form a parallel conformation in the solid state (Kastelic et al, 2010;Tsutsumi et al, 2011;Dayo-Owoyemi et al, 2019), which was also observed in our previous work [see the 2-aryl-2-hydroxyethyl fragment joined to the imidazole ring, in bold, in Figs.…”
Section: Introductionmentioning
confidence: 99%
“…Low aqueous solubility often results in poor therapeutic outcome. Different solubility techniques were used to enhance its solubility, namely: solid dispersion (Sayeed et al, 2016), use of cyclodextrins (Yurtdas et al 2011;Li et al 2016;Ahad et al, 2011) and cocrystal formation with dicarboxylic acid (Kastelic et al, 2010). However, no literature reveals formation of FLC-ILs.…”
Section: * Corresponding Authormentioning
confidence: 99%